Making Powder of Temulawak Rhizome (Cucum Axanthoriza) to Increase the Application - Aisyah Mentari; Ayus Diningsih (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
Background: Temulawak (Curcuma xanthorrhiza), has traditionally been widely used for medicinal purposes or as a drink to maintain health. Methods: Experimental Research conducted at the Traditional Medicine Laboratory, Pharmacy Study Program, Undergraduate Program, Aufa Royhan University. Result: Organoleptic test conducted that 8 out of 10 panelists liked the ginger powder drink. Conclusion: Organoleptic tests were carried out that 8 out of 10 panelists liked the temulawak powder drink.